5.17.3 Problems 201 to 300

Table 5.881: Second order, non-linear and homogeneous

#

ODE

Mathematica

Maple

11646

\[ {}y^{\prime \prime }-a \left (x y^{\prime }-y\right )^{v} = 0 \]

11647

\[ {}y^{\prime \prime }-k \,x^{a} y^{b} {y^{\prime }}^{r} = 0 \]

11648

\[ {}y^{\prime \prime }+\left (y^{\prime }-\frac {y}{x}\right )^{a} f \left (x , y\right ) = 0 \]

11649

\[ {}y^{\prime \prime } = a \sqrt {1+{y^{\prime }}^{2}} \]

11651

\[ {}y^{\prime \prime } = a \sqrt {{y^{\prime }}^{2}+b y^{2}} \]

11652

\[ {}y^{\prime \prime } = a \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} \]

11653

\[ {}y^{\prime \prime }-2 a x \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} = 0 \]

11654

\[ {}y^{\prime \prime }-a y \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} = 0 \]

11655

\[ {}y^{\prime \prime } = 2 a \left (c +b x +y\right ) \left (1+{y^{\prime }}^{2}\right )^{{3}/{2}} \]

11656

\[ {}y^{\prime \prime }+y^{3} y^{\prime }-y y^{\prime } \sqrt {y^{4}+4 y^{\prime }} = 0 \]

11657

\[ {}y^{\prime \prime }-f \left (y^{\prime }, a x +b y\right ) = 0 \]

11658

\[ {}y^{\prime \prime }-y f \left (x , \frac {y^{\prime }}{y}\right ) = 0 \]

11659

\[ {}y^{\prime \prime }-x^{n -2} f \left (y x^{-n}, y^{\prime } x^{1-n}\right ) = 0 \]

11660

\[ {}8 y^{\prime \prime }+9 {y^{\prime }}^{4} = 0 \]

11661

\[ {}a y^{\prime \prime }+h \left (y^{\prime }\right )+c y = 0 \]

11662

\[ {}x y^{\prime \prime }+2 y^{\prime }-x y^{n} = 0 \]

11663

\[ {}x y^{\prime \prime }+2 y^{\prime }+a \,x^{v} y^{n} = 0 \]

11664

\[ {}x y^{\prime \prime }+2 y^{\prime }+x \,{\mathrm e}^{y} = 0 \]

11665

\[ {}x y^{\prime \prime }+a y^{\prime }+b x \,{\mathrm e}^{y} = 0 \]

11666

\[ {}x y^{\prime \prime }+a y^{\prime }+b \,x^{5-2 a} {\mathrm e}^{y} = 0 \]

11667

\[ {}x y^{\prime \prime }+\left (y-1\right ) y^{\prime } = 0 \]

11668

\[ {}x y^{\prime \prime }-x^{2} {y^{\prime }}^{2}+2 y^{\prime }+y^{2} = 0 \]

11670

\[ {}2 x y^{\prime \prime }+{y^{\prime }}^{3}+y^{\prime } = 0 \]

11671

\[ {}x^{2} y^{\prime \prime } = a \left (y^{n}-y\right ) \]

11672

\[ {}x^{2} y^{\prime \prime }+a \left ({\mathrm e}^{y}-1\right ) = 0 \]

11674

\[ {}x^{2} y^{\prime \prime }+\left (a +1\right ) x y^{\prime }-x^{k} f \left (x^{k} y, x y^{\prime }+k y\right ) = 0 \]

11677

\[ {}x^{2} y^{\prime \prime }-\sqrt {a \,x^{2} {y^{\prime }}^{2}+b y^{2}} = 0 \]

11679

\[ {}4 x^{2} y^{\prime \prime }-x^{4} {y^{\prime }}^{2}+4 y = 0 \]

11680

\[ {}9 x^{2} y^{\prime \prime }+a y^{3}+2 y = 0 \]

11682

\[ {}x^{3} y^{\prime \prime }-a \left (x y^{\prime }-y\right )^{2} = 0 \]

11685

\[ {}x^{4} y^{\prime \prime }+a^{2} y^{n} = 0 \]

11686

\[ {}x^{4} y^{\prime \prime }-x \left (x^{2}+2 y\right ) y^{\prime }+4 y^{2} = 0 \]

11687

\[ {}x^{4} y^{\prime \prime }-x^{2} \left (x +y^{\prime }\right ) y^{\prime }+4 y^{2} = 0 \]

11688

\[ {}x^{4} y^{\prime \prime }+\left (x y^{\prime }-y\right )^{3} = 0 \]

11689

\[ {}y^{\prime \prime } \sqrt {x}-y^{{3}/{2}} = 0 \]

11690

\[ {}\left (a \,x^{2}+b x +c \right )^{{3}/{2}} y^{\prime \prime }-F \left (\frac {y}{\sqrt {a \,x^{2}+b x +c}}\right ) = 0 \]

11691

\[ {}x^{\frac {n}{n +1}} y^{\prime \prime }-y^{\frac {2 n +1}{n +1}} = 0 \]

11692

\[ {}f \left (x \right )^{2} y^{\prime \prime }+f \left (x \right ) f^{\prime }\left (x \right ) y^{\prime }-h \left (y, f \left (x \right ) y^{\prime }\right ) = 0 \]

11698

\[ {}y^{\prime \prime } y+{y^{\prime }}^{2}-y^{\prime } = 0 \]

11701

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}+{\mathrm e}^{x} y \left (c y^{2}+d \right )+{\mathrm e}^{2 x} \left (b +a y^{4}\right ) = 0 \]

11702

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}-y^{2} \ln \left (y\right ) = 0 \]

11703

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}-y^{\prime }+f \left (x \right ) y^{3}+y^{2} \left (\frac {f^{\prime \prime }\left (x \right )}{f \left (x \right )}-\frac {{f^{\prime }\left (x \right )}^{2}}{f \left (x \right )^{2}}\right ) = 0 \]

11704

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}+f \left (x \right ) y^{\prime }-f^{\prime }\left (x \right ) y-y^{3} = 0 \]

11705

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}+f^{\prime }\left (x \right ) y^{\prime }-f^{\prime \prime }\left (x \right ) y+f \left (x \right ) y^{3}-y^{4} = 0 \]

11706

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}+a y y^{\prime }+b y^{2} = 0 \]

11707

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}+a y y^{\prime }-2 y^{2} a +b y^{3} = 0 \]

11708

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}-\left (-1+a y\right ) y^{\prime }+2 a^{2} y^{2}-2 y^{3} b^{2}+a y = 0 \]

11709

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}+\left (-1+a y\right ) y^{\prime }-y \left (1+y\right ) \left (y^{2} b^{2}-a^{2}\right ) = 0 \]

11710

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}+\left (\tan \left (x \right )+\cot \left (x \right )\right ) y y^{\prime }+\left (\cos \left (x \right )^{2}-n^{2} \cot \left (x \right )^{2}\right ) y^{2} \ln \left (y\right ) = 0 \]

11711

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}-f \left (x \right ) y y^{\prime }-g \left (x \right ) y^{2} = 0 \]

11712

\[ {}y^{\prime \prime } y-{y^{\prime }}^{2}+\left (g \left (x \right )+y^{2} f \left (x \right )\right ) y^{\prime }-y \left (g^{\prime }\left (x \right )-f^{\prime }\left (x \right ) y^{2}\right ) = 0 \]

11713

\[ {}y^{\prime \prime } y-3 {y^{\prime }}^{2}+3 y y^{\prime }-y^{2} = 0 \]

11714

\[ {}y^{\prime \prime } y-a {y^{\prime }}^{2} = 0 \]

11715

\[ {}y^{\prime \prime } y+a \left (1+{y^{\prime }}^{2}\right ) = 0 \]

11716

\[ {}y^{\prime \prime } y+a {y^{\prime }}^{2}+b y^{3} = 0 \]

11717

\[ {}y^{\prime \prime } y+a {y^{\prime }}^{2}+b y y^{\prime }+c y^{2}+d y^{1-a} = 0 \]

11718

\[ {}y^{\prime \prime } y+a {y^{\prime }}^{2}+f \left (x \right ) y y^{\prime }+g \left (x \right ) y^{2} = 0 \]

11719

\[ {}y^{\prime \prime } y+a {y^{\prime }}^{2}+b y^{2} y^{\prime }+c y^{4} = 0 \]

11720

\[ {}y^{\prime \prime } y-\frac {\left (a -1\right ) {y^{\prime }}^{2}}{a}-f \left (x \right ) y^{2} y^{\prime }+\frac {a f \left (x \right )^{2} y^{4}}{\left (2+a \right )^{2}}-\frac {a f^{\prime }\left (x \right ) y^{3}}{2+a} = 0 \]

11722

\[ {}y^{\prime \prime } \left (x +y\right )+{y^{\prime }}^{2}-y^{\prime } = 0 \]

11723

\[ {}y^{\prime \prime } \left (x -y\right )+2 y^{\prime } \left (1+y^{\prime }\right ) = 0 \]

11724

\[ {}y^{\prime \prime } \left (x -y\right )-\left (1+y^{\prime }\right ) \left (1+{y^{\prime }}^{2}\right ) = 0 \]

11725

\[ {}y^{\prime \prime } \left (x -y\right )-h \left (y^{\prime }\right ) = 0 \]

11729

\[ {}2 y^{\prime \prime } y-{y^{\prime }}^{2}-8 y^{3} = 0 \]

11730

\[ {}2 y^{\prime \prime } y-{y^{\prime }}^{2}-8 y^{3}-4 y^{2} = 0 \]

11731

\[ {}2 y^{\prime \prime } y-{y^{\prime }}^{2}-4 \left (x +2 y\right ) y^{2} = 0 \]

11732

\[ {}2 y^{\prime \prime } y-{y^{\prime }}^{2}+\left (a y+b \right ) y^{2} = 0 \]

11734

\[ {}2 y^{\prime \prime } y-{y^{\prime }}^{2}+\left (b x +a y\right ) y^{2} = 0 \]

11735

\[ {}2 y^{\prime \prime } y-{y^{\prime }}^{2}-3 y^{4} = 0 \]

11737

\[ {}2 y^{\prime \prime } y-{y^{\prime }}^{2}+3 f \left (x \right ) y y^{\prime }+2 \left (f \left (x \right )^{2}+f^{\prime }\left (x \right )\right ) y^{2}-8 y^{3} = 0 \]

11739

\[ {}2 y^{\prime \prime } y-3 {y^{\prime }}^{2} = 0 \]

11740

\[ {}2 y^{\prime \prime } y-3 {y^{\prime }}^{2}-4 y^{2} = 0 \]

11741

\[ {}2 y^{\prime \prime } y-3 {y^{\prime }}^{2}+y^{2} f \left (x \right ) = 0 \]

11742

\[ {}2 y^{\prime \prime } y-6 {y^{\prime }}^{2}+\left (1+a y^{3}\right ) y^{2} = 0 \]

11743

\[ {}2 y^{\prime \prime } y-{y^{\prime }}^{2} \left (1+{y^{\prime }}^{2}\right ) = 0 \]

11746

\[ {}3 y^{\prime \prime } y-5 {y^{\prime }}^{2} = 0 \]

11747

\[ {}4 y^{\prime \prime } y-3 {y^{\prime }}^{2}+4 y = 0 \]

11748

\[ {}4 y^{\prime \prime } y-3 {y^{\prime }}^{2}-12 y^{3} = 0 \]

11749

\[ {}4 y^{\prime \prime } y-3 {y^{\prime }}^{2}+a y^{3}+b y^{2}+c y = 0 \]

11750

\[ {}4 y^{\prime \prime } y-3 {y^{\prime }}^{2}+\left (6 y^{2}-\frac {2 f^{\prime }\left (x \right ) y}{f \left (x \right )}\right ) y^{\prime }+y^{4}-2 y^{\prime } y^{2}+g \left (x \right ) y^{2}+f \left (x \right ) y = 0 \]

11751

\[ {}4 y^{\prime \prime } y-5 {y^{\prime }}^{2}+y^{2} a = 0 \]

11752

\[ {}12 y^{\prime \prime } y-15 {y^{\prime }}^{2}+8 y^{3} = 0 \]

11753

\[ {}n y y^{\prime \prime }-\left (n -1\right ) {y^{\prime }}^{2} = 0 \]

11755

\[ {}a y y^{\prime \prime }+b {y^{\prime }}^{2}-\frac {y y^{\prime }}{\sqrt {c^{2}+x^{2}}} = 0 \]

11756

\[ {}a y y^{\prime \prime }-\left (a -1\right ) {y^{\prime }}^{2}+\left (2+a \right ) f \left (x \right ) y^{2} y^{\prime }+f \left (x \right )^{2} y^{4}+a f^{\prime }\left (x \right ) y^{3} = 0 \]

11757

\[ {}\left (a y+b \right ) y^{\prime \prime }+c {y^{\prime }}^{2} = 0 \]

11758

\[ {}x y y^{\prime \prime }+x {y^{\prime }}^{2}-y y^{\prime } = 0 \]

11760

\[ {}x y y^{\prime \prime }-x {y^{\prime }}^{2}+y y^{\prime }+x \left (d +a y^{4}\right )+y \left (c +b y^{2}\right ) = 0 \]

11761

\[ {}x y y^{\prime \prime }-x {y^{\prime }}^{2}+a y y^{\prime }+b x y^{3} = 0 \]

11762

\[ {}x y y^{\prime \prime }+2 x {y^{\prime }}^{2}+a y y^{\prime } = 0 \]

11763

\[ {}x y y^{\prime \prime }-2 x {y^{\prime }}^{2}+\left (1+y\right ) y^{\prime } = 0 \]

11764

\[ {}x y y^{\prime \prime }-2 x {y^{\prime }}^{2}+a y y^{\prime } = 0 \]

11765

\[ {}x y y^{\prime \prime }-4 x {y^{\prime }}^{2}+4 y y^{\prime } = 0 \]

11766

\[ {}x y y^{\prime \prime }+\left (\frac {a x}{\sqrt {b^{2}-x^{2}}}-x \right ) {y^{\prime }}^{2}-y y^{\prime } = 0 \]

11767

\[ {}x \left (x +y\right ) y^{\prime \prime }+x {y^{\prime }}^{2}+y^{\prime } \left (x -y\right )-y = 0 \]

11768

\[ {}2 x y y^{\prime \prime }-x {y^{\prime }}^{2}+y y^{\prime } = 0 \]

11769

\[ {}x^{2} \left (y-1\right ) y^{\prime \prime }-2 x^{2} {y^{\prime }}^{2}-2 x \left (y-1\right ) y^{\prime }-2 y \left (y-1\right )^{2} = 0 \]

11770

\[ {}x^{2} \left (x +y\right ) y^{\prime \prime }-\left (x y^{\prime }-y\right )^{2} = 0 \]

11771

\[ {}x^{2} \left (x -y\right ) y^{\prime \prime }+a \left (x y^{\prime }-y\right )^{2} = 0 \]

11772

\[ {}2 x^{2} y y^{\prime \prime }-x^{2} \left (1+{y^{\prime }}^{2}\right )+y^{2} = 0 \]